ISLAMIC ECONOMICS AS AN ALTERNATIVE ECONOMI SYSTEM: A THEMATIC CONCEPTUAL LITERATURE - Abdul Gafur Rinaldi (PT. Samudra Solusi Profesional, 2025)
Islamic economics has increasingly gained scholarly attention as an alternative economic system amid growing dissatisfaction with conventional capitalist and socialist frameworks. The global economy continues to face persistent challenges such as financial instability, widening income inequality, ethical degradation, and recurrent economic crises, which expose structural weaknesses in dominant economic paradigms. Islamic economics offers a value-based framework grounded in Sharia principles that integrates ethical considerations, social justice, and economic efficiency. This article aims to conceptually review Islamic economics as an alternative economic system through a thematic literature review approach. By systematically synthesizing theoretical and conceptual studies from both classical and contemporary literature, this article identifies core themes that define Islamic economics, including its philosophical foundations, normative principles, institutional mechanisms, and socio-economic objectives. The review highlights how Islamic economics differs fundamentally from conventional systems by emphasizing the prohibition of interest (riba), risk-sharing mechanisms, equitable wealth distribution, and moral accountability. Furthermore, this article discusses the relevance of Islamic economics in addressing modern economic challenges, particularly in developing countries such as Indonesia, where economic inequality and financial exclusion remain significant issues. Secondary data from national institutions indicate a growing role of Islamic financial institutions and halal industries in supporting inclusive economic development. Despite its potential, the literature also reveals several challenges related to conceptual clarity, institutional implementation, and integration within the global economic system. This article contributes to the academic discourse by providing a structured conceptual understanding of Islamic economics and identifying research gaps for future empirical and policy-oriented studies. The findings are expected to serve as a theoretical reference for scholars, policymakers, and practitioners interested in developing alternative, ethical, and sustainable economic systems.